Intimations of mortality : medical decision-making at the end of life - Reich, Barbara A. (Cambridge : Cambridge University Press, 2022)
In Intimations of Mortality, Barbara Reich offers an empirically-based critique of the failures of end-of-life communication and decision-making in the United States. Using England and Canada as occasional foils, Reich explores why U.S. physicians, patients, and families struggle to have the conversations necessary to provide seriously ill and dying patients with medical care consistent with their preferences. Reich also shows how a number of different factors -including payment mechanisms, liability fears, cultural phenomena, communication avoidance, death denial, and clinical uncertainty -impact physician-patient communication and medical decision-making, leave patients and families without the tools they need to make informed choices, and instead leave the default practices in place. Ultimately, this groundbreaking analysis unveils the interconnectedness of the many obstacles to better communication and decision-making in end-of-life communications and offers much-needed suggestions for improvement.
The conundrum : how much medical care is 'enough'? -- Our health care 'system' : the good, the bad, and the probably unfixable -- Autonomy and informed consent in the real world -- The denial of death and its sequelae -- Disorders of consciousness and the meaning of life -- More barriers to good communication -- Palliative and hospice care : misunderstandings and lost opportunities -- Rational apathy and the role of uncertainty -- The crucible : making decisions for incapacitated patients -- Resolving conflicts at the end of life : three models -- At the endd of the day -- Coda.
Title from publisher's bibliographic system (viewed on 11 Mar 2022).
Keywords: Terminal care -- Law and legislation -- United States